Service Quality Attributes and Customers Usage of E-banking Payment Transactions in Developing Countries: A Study of Tanzania - Morris, Ally; Mbamba, Ulingeta O.L.; Kessy, Severine (University of Dar es Salaam Library Journal, 2024)
This paper aimed to examine the effects of service quality measures of information system success on customers ' usage of e-banking payment transactions in Tanzania. It was hypothesised that Service quality measures of information systems positively influence the usage of e-banking payment transactions. This hypothesis was tested by the partial least square structural equation modelling technique (PLS-SEM) through the use of SmartPLS3. The study is informed by the information system success theory and the Unified Theory of Acceptance and Use of Technology (UTAUT). The study adopted a cross-sectional survey approach, where 400 respondents were involved. The results show that responsiveness, privacy, assurance, empathy, and customer support have a significant positive influence on customers' usage of e-banking payment transactions. The findings imply that customers who are highly concerned with the availability of high-quality services in e-banking have the potential to enhance the usage of e-banking payment transactions. Thus, managers in the banking industry are urged to uplift the level of service quality as a strategy to elevate customers' usage of e-banking payment transactions. Future research is recommended to look into the influence of service quality measures on information system success and usage of e-payment in other sectors like the public transportation system, and schools.